Is socioeconomic position associated with risk of attempted suicide in rural Sri Lanka? A cross-sectional study of 165 000 individuals. Issue 3 (22nd March 2017) - Knipe, D W; Gunnell, D; Pieris, R; Priyadarshana, C; Weerasinghe, M; Pearson, M; Jayamanne, S; Dawson, A H; Mohamed, F; Gawarammana, I; Hawton, K; Konradsen, F; et al.
Abstract : Background: Lower socioeconomic position (SEP) is associated with an increased risk of suicidal behaviour in high-income countries, but this association is unclear in low-income and middle-income countries. Methods: We investigated the association of SEP with attempted suicide in a cross-sectional survey of 165 233 Sri Lankans. SEP data were collected at the household (assets, social standing (highest occupation of a household member), foreign employment and young (≤40 years) female-headed households) and individual level (education and occupation). Respondent-reported data on suicide attempts in the past year were recorded. Random-effects logistic regression models, accounting for clustering, were used to investigate the association of SEP with attempted suicide. Results: Households reported 398 attempted suicides in the preceding year (239 per 100 000). Fewer assets (OR 3.2, 95% CI 2.4 to 4.4) and having a daily wage labourer (ie, insecure/low-income job; OR 2.3, 95% CI 1.6 to 3.2) as the highest occupation increased the risk of an attempted suicide within households. At an individual level, daily wage labourers were at an increased risk of attempted suicide compared with farmers. The strongest associations were with low levels of education (OR 4.6, 95% CI 2.5 to 8.4), with a stronger association in men than women. Conclusions: We found that indicators of lower SEP are associated with increased risk of attempted suicide in rural Sri Lanka. Longitudinal studies with objective measures of suicide attempts are needed to confirm this association. Trial registration number: NCT01146496; Pre-results .